Necesidad de agregar al artículo 413 del código de procedimiento civil y al artículo 410 del código de comercio, el reconocimiento ante el notario y la inscripción en el registro mercantil como requisito de la letra de cambio - Briceño Torres, Luis Ángel (2016)
This paper entitled "NEED TO ADD TO ARTICLE 413 OF THE CODE OF CIVIL PROCEDURE AND ARTICLE 410 OF THE CODE OF TRADE, BEFORE THE NOTARY ACKNOWLEDGMENT AND COMMERCIAL REGISTRATION REQUIREMENT OF THE POINT OF CHANGE", deals with the study of an issue of a legal, social and economic as summarized in the following. The right to legal certainty, that according to the Constitution of the Republic of Ecuador, is based on the existence of clear legal standards, and previous public that can be applied by the competent authorities in safeguarding the rights and interests of the people, has no effective enforcement regarding effectively guarantee the rights of the people involved as a creditor and debtor in the legal obligation arising from underwriting and acceptance of the draft. This is due to the Civil Procedure Code and the Commercial Code in force in Ecuadorian law, no legal provision that expressly establish the obligation of the parties to appear before a Notary Public, for recognition of the bill of exchange and value containing the same, not stated as a requirement for the validity of the enforcement, the parties attend before the registrar in order to proceed with the registration of this document. The lack of requirements as those that have been noted in the preceding paragraphs, causes in Ecuadorian society comes the bill of exchange to be used frequently, fraudulently by creditors or bondholders, who alter the value of the obligation of the debtor , and that there are cases in which the taxpayer of the obligation that is the debtor claims the lack of obligation jeopardizing the interests of the creditor. The problem as described above is that in this job board by filing a conceptual theoretical elements, doctrinal and legal and comparative law rules, and results obtained through a process conducted field research based on the implementation of the survey and interviews, all of which give the basis for the conclusion of the approach through an amendment to the Code of Civil Procedure and the Code of Commerce, for which the corresponding proposal is presented at the end of job.